Adolescent, caregiver and community experiences with a gender transformative, social emotional learning intervention - Megan Cherewick; Sarah Lebu; Christine Su; Lisa Richards; Prosper F. Njau; Ronald E. Dahl (BMC, 2021)
Abstract Background Inequitable gender norms, beliefs and behaviors, are shaped by learning experiences during key developmental stages in an individual's life course, and can have negative impacts on health and well-being outcomes. Very early adolescence represents one stage when formative learning experiences about gender inequity can have the potential to support or hinder more equitable gender norms, beliefs and behaviors. The aim of this qualitative study was to evaluate the effect of a gender transformative, social emotional learning intervention for very young adolescents (VYAs) that included experiential learning with peers, parents/caregivers and community members. Methods This study examined the effects of an intervention designed to provide social emotional learning opportunities for adolescents ages 10-11 in Dar es Salaam, Tanzania. The qualitative sample included 279 participants. Qualitative methods included 102 in-depth interviews with VYAs, 22 focus groups with 117 VYAs, 60 in-depth interviews with parents/caregivers and 54 participant observations. A grounded theory approach was used to identify emergent themes. Results Participants reported growth in targeted areas of social emotional mindsets and skills, including a shift in gender norms, beliefs and behaviors. VYAs reported that experiential learning in mixed gender teams provided opportunities to actively practice and reflect on gender norms, beliefs and behaviors. VYAs also reported active practice of social emotional mindsets and skills with peers, parents/caregivers and the community. Parents/caregivers reported changes in VYAs' social emotional mindsets and skills within the home, with the community and with siblings and peers. Both adolescents and parent/caregivers reported positive change towards more equitable gender norms, beliefs and behaviors through participation in experiential learning activities and reflective discussions. Conclusions These findings suggest that an intervention providing social and emotional experiential learning opportunities during the developmental window of very young adolescence can be effective in transforming gender norms, beliefs and behaviors. Involvement of peers, parents/caregivers and community members was effective at supporting learning social emotional mindsets and skills in VYAs. Findings encourage local and global adolescent programming to include gender transformative content paired with social emotional experiential learning with peers, family and the community and can stimulate positive change in gender norms, beliefs and behaviors to promote gender equity.